2022
DOI: 10.1002/qua.26906
|View full text |Cite
|
Sign up to set email alerts
|

Strain effects on the structural, electronic, optical and thermoelectric properties of Si2SeS monolayer with puckered honeycomb structure: A first‐principles study

Abstract: In this paper, the first‐principles calculations based on the Density Functional Theory (DFT) have been used to study the effect of strain on the structural, electronic, optical and thermoelectric properties of the puckered Si2SeS monolayer. Our calculations show that the puckered Si2SeS monolayer has an indirect band gap of 1.30 eV at the equilibrium state, which can be tuned by biaxial strain and the semiconductor–metal phase transition occurs at −10%. Interestingly, a high absorption coefficient exceeds 107… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 74 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…[ 28–30 ] Janus group‐IV dichalcogenide monolayered including Ge 2 SSe, SiSeS, puckered Si 2 SeS, and SnSSe monolayers have been systematically studied within the framework of first‐principles calculations. [ 31–35 ] The results show that those monolayers exhibit good thermodynamic stability, which allows them to be used in energy conversion, sensors, and optoelectronic applications. Recently, bismuth‐based 2D Janus monolayers have been successfully fabricated, [ 36 ] with Bi atomic planes stacked in between the atomic planes of Te and Cl/Br atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28–30 ] Janus group‐IV dichalcogenide monolayered including Ge 2 SSe, SiSeS, puckered Si 2 SeS, and SnSSe monolayers have been systematically studied within the framework of first‐principles calculations. [ 31–35 ] The results show that those monolayers exhibit good thermodynamic stability, which allows them to be used in energy conversion, sensors, and optoelectronic applications. Recently, bismuth‐based 2D Janus monolayers have been successfully fabricated, [ 36 ] with Bi atomic planes stacked in between the atomic planes of Te and Cl/Br atoms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies demonstrate that strain engineering has been employed to enhance the thermoelectric and optical properties of 2D materials. In a previous work, it was reported that the electronic figure of merit (ZTe) of the puckered Si2SeS monolayer reaches 2.55 under a tensile biaxial strain of 6% [16]. Moreover, using first-principles calculations, the electronic structure, optical and thermoelectric properties of the Janus T-phase SiSeS monolayer have been examined under biaxial strain, and a large electronic figure of merit (ZTe) of 7.0 at 300 K has been found with the combination of compressive biaxial strain and p-type doping in the Janus SiSeS monolayer [17].…”
Section: Introductionmentioning
confidence: 99%